Good manufacturing practices personal hygiene and practices in food manufacturing - Roseman, Arnold; Pennsylvania State University (University Park, Pa. Pennsylvania Statue University, 1993)
Describes personal hygiene needed for safe food handling and manufacturing.
VHS
Keywords: Food industry and trade -- Safety measures; Food industry and trade -- Sanitation; Food handling; Food contamination -- Prevention